Association of Human Leukocyte Antigen Gene Variants rs13192471 and rs6457617 with Rheumatoid Arthritis Susceptibility: A Case-control Study from North-western India - Indermohan Singh Sandhu; Hemender Singh; Anupama Mahajan; Gurinder Mohan; Swarkar Sharma; Prakash Singh; Simranpreet Kaur; Amarjit Singh Bhanwer (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Rheumatoid Arthritis (RA) is a systemic, chronic, inflammatory, and autoimmune disease which is characterised by the progressive ruination of joint structures. The Human Leukocyte Antigens (HLA) genes: HLA-DRB1 and HLA-DQB1, belonging to HLA family, presented on human chromosome six, are involved in the immune system. Various studies involving Genome-wide Association Studies (GWAS), meta-analysis, and replication studies have shown the association of HLA-DRB1 variant rs13192471 and HLA-DQB1 variant rs6457617 with RA susceptibility in different population groups. Aim: To perform a replication case-control based association study of variants rs13192471 and rs6457617, in order to determine their association with RA, in an independent cohort from the population of North-western India. Materials and Methods: The Case-control study conducted at Sri Guru Ram Das Institute of Medical Sciences and Research, Amritsar, Punjab, India, duration of the study was, from May 2019 to June 2022. In this study, Deoxyribonucleic Acid (DNA) was isolated from 188 RA cases and 310 healthy controls, followed by qualitative and quantitative analyses. The genotyping was performed on a Real Time-polymerase Chain Reaction (RT-PCR) using TaqMan Allele Discrimination Assay. Statistical power of the study was estimated using PS: Power and sample size calculator version 3.1. Results: The statistical analysis of the genotyping data showed a significant association (p=0.005) of variant rs13192471 with RA susceptibility, whereas the variant rs6457617 did not show an association (p=0.275) with RA in the studied population cohort. Conclusion: The present study successfully replicated the association of HLA-DRB1 variant rs13192471 in the population group of North-western India. It is pertinent to screen these variants for RA susceptibility in other population groups of India before their use as potential genetic biomarkers in the Indian population.